Molecular characterization of the giant freshwater prawn (Macrobrachium rosenbergii) beta-actin gene promoter - Junjun Yan (PeerJ, 2018)
Constitutive promoters are important tools for gene function studies and transgenesis. The Beta-actin (actb1) gene promoter has been isolated from many species but remains to be cloned from the giant freshwater prawn (Macrobrachium rosenbergii). In this study, we cloned and characterized the Mractb1 gene promoter. Two alternative promoters were identified for the Mractb1 gene, which direct the generation of two transcripts with different 5′ untranslated regions. Three CpG islands were predicted in the upstream sequence, which are intimately related to transcription initiation and promoter activity. In addition to the CCAAT-box and the CArG-box, molecular dissection of the flanking sequence revealed the existence of one negative and two positive elements in the upstream region and the first intron. Finally, the Mractb1 promoter demonstrated comparative activity to the carp (Cyprinus carpio) actb1 promoter. Our investigations provide a valuable genetic tool for gene function studies and shed light on the regulation of the Mractb1 gene.